Synthesis of small cyclic peptides constrained with 3-(3-aminomethylphenyl)propionic acid linkers using free radical-mediated macrocyclization - Balraju, V.; Reddy, D. Srinivasa; Periasamy, M.; Iqbal, Javed (Tetrahedron Letters, 2005)
In this letter, we report that small peptides (di- and tri-) having a 3-bromobenzyl group at the C-termini and an acryloyl group at the N-termini undergo an efficient Bu3SnH-AlBN mediated intramolecular free radical cyclization to afford cyclic peptides in good yields. We also propose that these cyclizations are occurring via a pre-organized acyclic structure dictated by a reverse turn (gamma/beta-turn). (c) 2005 Published by Elsevier Ltd.